Patterns of Communication Between BPD and Community in Village Development - Etika Faktania; Ainur Rochmaniah (Indonesian Journal of Cultural and Community Development, 2023)
The formulationin this study is how the communication pattern between BDP and the community in the development of the Sepande Village is. The purpose of this study was to determine the pattern of communication between BPD and the community in the development of Sepande Village. This study uses a qualitative descriptive approach because it is able to describe, and answer problems in a concise manner. Data collected through interviews. And using the theory of communication patterns. The results of this study indicate that the communication pattern between the BPD and the community in the development of the Sepande Village is a one- way, two-way and multi-way communication pattern.